PENGARUH PENDIDIKAN KESEHATAN SECARA INDIVIDUAL TENTANG PEMBATASAN ASUPAN CAIRAN TERHADAP INTERDIALYTIC WEIGHT GAIN (IDWG) PADA PASIEN HEMODIALISIS - Dhini " Febriana; Bayhakki " "; Veny " Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract  Health education about fluid intake restraction should be given to patient on hemodialysis (HD) in order to prevent complications.  The purpose of this research was to determine the influence of health education with individual approach about fluid intake restriction towards interdialytic weight gain (IDWG) in patients with hemodialysis. The design of this research was quasy experiment. 32 respondens were taken by using purposive sampling method. Measuring instruments was analog scale. Data were analysed by using dependent t test and independent t test. Most respondents were aged 56-65 years (28,1%), with equal number between men and women (50%), most of respondents didn’t work (37,5%), must of length of HD were 12-24 months (40,6%). The result of this research showed there was influence health education using individual methods of restricting fluid intake towards IDWG in patients with hemodialysis p value (0,016) <  α (0,05). Nurses are suggested to provide nursing care about restricting fluid intake to prevent complications in order to improve the quality of life of patients. Keywords: hemodialysis, individual method, health education, fluid intake restraction